2014
DOI: 10.1149/2.0101410jss
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Bismuth Nanocrystals in Bi2O3Thin Films Grown at 300 K by Pulsed Laser Deposition for Thermoelectric Applications

Abstract: Bismuth nanocrystals were embedded in amorphous Bi2O3 thin films grown under a nitrogen atmosphere at room temperature using pulsed laser deposition. As-grown Bi2O3-Bi thin films showed a high electrical conductivity of approximately 769 S/cm at 320 K, and the samples annealed in two steps at 200 and 300°C consisted of amorphous Bi2O3, bismuth nanocrystals in the crystallized β-Bi2O3 phase. The mixture phase of the bismuth nanocrystals and β-Bi2O3 enhanced the thermoelectric properties at room temperature. Sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
(24 reference statements)
2
5
0
Order By: Relevance
“…XRD measurements were performed to study the structural changes in the Bi 2 O 3 particles and PAM/Bi 2 O 3 hydrogel before and after laser irradiation. Figure c shows X‐ray diffraction patterns of the Bi 2 O 3 powders in the 2 θ range from 5° to 80° before and after laser marking at the laser power of 35.3 W. The unmarked Bi 2 O 3 powders show four main reflections at approximately 2 θ = 27.8°, 31.6°–32.7°, 45.9°–48°, and 54°–57.6°, which agree with the characteristics of Bi 2 O 3 reported in literature . A zoom‐in of the region between 25° and 45° is shown in Figure d.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…XRD measurements were performed to study the structural changes in the Bi 2 O 3 particles and PAM/Bi 2 O 3 hydrogel before and after laser irradiation. Figure c shows X‐ray diffraction patterns of the Bi 2 O 3 powders in the 2 θ range from 5° to 80° before and after laser marking at the laser power of 35.3 W. The unmarked Bi 2 O 3 powders show four main reflections at approximately 2 θ = 27.8°, 31.6°–32.7°, 45.9°–48°, and 54°–57.6°, which agree with the characteristics of Bi 2 O 3 reported in literature . A zoom‐in of the region between 25° and 45° is shown in Figure d.…”
Section: Resultssupporting
confidence: 87%
“…Compared to the unmarked Bi 2 O 3 powders, the laser‐marked Bi 2 O 3 powders exhibit several new peaks at approximately 2 θ = 26.8°, 35.9°, and 37.5°, which are in agreement with the XRD characteristics of bismuth metal. Eom et al found the same characteristic peaks in XRD patterns, which were attributed to Bi metal . Figure e and f show XRD patterns of the PAM/Bi 2 O 3 ‐1% hydrogels in the 2 θ range from 5° to 70° and 25° to 45°, respectively, before and after laser marking at the laser power of 35.3 W. In the spectrum of the unmarked PAM/Bi 2 O 3 hydrogel, the characteristic peaks attributed to Bi 2 O 3 can be found.…”
Section: Resultsmentioning
confidence: 54%
“…It should be stressed that the calculated value of  min = 0.45 W m -1 K -1 is smaller than the thermal conductivity measured at room temperature for α-Bi 2 O 3 which turns out to be 1.3 W m -1 K -1 [69]. Therefore, we consider that there is room for improvement in the decrease of the thermal conductivity of bismite both at room pressure and at HP conditions for thermoelectric applications [70].…”
Section: Thermodynamic Properties Of Bismitementioning
confidence: 79%
“…electrical resistivity of bismuth nanocrystals can be reduced and Seebeck coefficient can be increased when the metal is covered with Bi 2 O 3 layer and this effect is directly associated with the crystal structure of the oxide. The mixture of metallic bismuth and β‐Bi 2 O 3 seems to be the most effective combination to enhance the power factor of this nanostructure . Since the impact of metallic Bi nanowires content on nanocomposites properties was the main subject of the presented study, the oxide layer covering Bi NWs was considered as an unwanted factor which influence should be minimized.…”
Section: Resultsmentioning
confidence: 99%